Interaksi Simbolik dan Ekologi Media Dalam Proses Keterlibatan Sebagai Roleplayer - Meydhita Stevanny; Muhammad Adi Pribadi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Roleplayer is a game that played by acting as a certain character. Also in roleplaying there is a use of language, symbols and words to interact with each other and human dependence on the use of media when playing is one of the interests for researchers. This study aims to determine the role of symbolic interaction and media ecology in roleplaying games by focusing on out of character on twitter, the theory used in this study is symbolic interaction theory, media ecology theory. The research approach used is qualitative description with ethnographic methods. Researchers collected data by conducting participant observation, in-depth interviews with several roleplayer players out of character and library studies. The conclusion of this study is that individuals are involved in several stages in the process of involvement of someone roleplayer, namely: introduction, finding information, determining character, and starting to play. In roleplayer there is the use of language, certain words and symbols, expectations (Pygmalion effect), and rules in play. Roleplayer adalah permainan yang dimainkan dengan berperan sebagai karakter tertentu. Permainan roleplayer menggunakan bahasa, simbol serta kata-kata untuk saling berinteraksi serta ketergantungan manusia dalam penggunaan media ketika bermain. Penelitian ini bertujuan untuk mengetahui peran interaksi simbolik dan ekologi media dalam permainan roleplayer dengan berfokus pada out of character di media sosial Twitter. Penelitian ini menggunakan teori interaksi simbolik dan ekologi media. Pendekatan penelitian yang digunakan adalah kualitatif deskripsi dengan metode etnografi. Peneliti mengumpulkan data dengan melakukan observasi partisipan, wawancara mendalam dengan beberapa pemain roleplayer out of character dan studi kepustakaan. Kesimpulan dari penelitian ini adalah individu terlibat dalam beberapa tahapan dalam proses keterlibatan seseorang permainan roleplayer yaitu: perkenalan, mencari informasi, menentukan karakter, dan mulai bermain. Di dalam roleplayer terdapat penggunaan bahasa, kata-kata serta simbol-simbol tertentu, harapan-harapan (pygmalion effect), dan peraturan-peraturan dalam bermain.